An investigation into the use of simile and parallelism in the novel “a thousand splendid suns” by khaled hosseini and its vietnamese translational equivalent - Nguyễn Thị Thùy Dung (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study aims at examining the use of similes and parallelisms in the novel “A Thousand Splendid Suns” and its Vietnamese version. The study is carried out to discover the translator‟s tendency to apply translation methods and how efficiently she uses them to translate the stylistic devices into Vietnamese. In addition to, the loss and gain in translating process from English to Vietnamese in terms of lexis and meaning are also mentioned